2019
DOI: 10.1111/fima.12300
|View full text |Cite
|
Sign up to set email alerts
|

Cryptocurrencies: Stylized facts on a new investible instrument

Abstract: We present stylized facts on the asset pricing properties of cryptocurrencies: summary statistics on cryptocurrency return properties and measures of common variation for secondary market returns on 222 digital coins. In our sample, secondary market returns of all other currencies are strongly correlated with Bitcoin returns. We also provide some investment characteristics of a sample of 64 initial coin offerings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(31 citation statements)
references
References 24 publications
(22 reference statements)
2
29
0
Order By: Relevance
“…Before proceeding to the analysis we would also like to point out that there is a rapidly expanding empirical literature on ICOs. Hu et al (2018), Dittmar and Wu (2018), Benedetti and Kostovetsky (2018) and Bianchi and Dickerson (2018) study factors that affect the returns of investments in token markets. and De Jong et al (2018) study the determinants of successful attempts to raise funds with an ICO.…”
Section: Related Literaturementioning
confidence: 99%
“…Before proceeding to the analysis we would also like to point out that there is a rapidly expanding empirical literature on ICOs. Hu et al (2018), Dittmar and Wu (2018), Benedetti and Kostovetsky (2018) and Bianchi and Dickerson (2018) study factors that affect the returns of investments in token markets. and De Jong et al (2018) study the determinants of successful attempts to raise funds with an ICO.…”
Section: Related Literaturementioning
confidence: 99%
“…Similarly, Ankenbrand and Bieri [35] concluded that cryptocurrencies can be seen as an individual asset class. Additional studies [11,36,37] offer valuable insides and facts about cryptocurrencies as a new financial asset, which makes them an effective diversification tool.…”
Section: Cryptocurrencies-a Short Overviewmentioning
confidence: 99%
“…Before proceeding to the analysis we would also like to point out that there is a rapidly expanding empirical literature on ICOs. Hu et al (2018), Dittmar andWu (2018), Benedetti andKostovetsky (2018) and Bianchi and Dickerson (2018) study factors that affect the returns of investments in token markets. and De Jong et al (2018) study the determinants of successful attempts to raise funds with an ICO.…”
Section: Related Literaturementioning
confidence: 99%